2016
DOI: 10.1016/j.jphs.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Suplatast tosilate alleviates nasal symptoms through the suppression of nuclear factor of activated T-cells-mediated IL-9 gene expression in toluene-2,4-diisocyanate-sensitized rats

Abstract: Histamine H1 receptor (H1R) gene is upregulated in patients with pollinosis; its expression level is highly correlated with the nasal symptom severity. Antihistamines are widely used as allergy treatments because they inhibit histamine signaling by blocking H1R or suppressing H1R signaling as inverse agonists. However, long-term treatment with antihistamines does not completely resolve toluene-2,4-diisocyanate (TDI)-induced nasal symptoms, although it can decrease H1R gene expression to the basal level, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…suppression of both PKCδ signaling and NFAT signaling markedly alleviated TDI-induced nasal symptoms in TDI-sensitized rats (14). The in vitro experiments data suggest that WGE and Awa-tea suppress PKCδ signaling and NFAT signaling, respectively.…”
Section: The Journal Of Medical Investigation Vol 65 August 2018mentioning
confidence: 76%
See 3 more Smart Citations
“…suppression of both PKCδ signaling and NFAT signaling markedly alleviated TDI-induced nasal symptoms in TDI-sensitized rats (14). The in vitro experiments data suggest that WGE and Awa-tea suppress PKCδ signaling and NFAT signaling, respectively.…”
Section: The Journal Of Medical Investigation Vol 65 August 2018mentioning
confidence: 76%
“…Recently, we have found that treatment with Awa-tea in combination with anti-histamine markedly improved allergic symptoms in TDI-sensitized rats (Nakano and Mizuguchi, manuscript in preparation). This ef-fect of Awa-tea is similar to that of suplatast that suppresses NFATmediated IL-9 gene expression (14). Therefore, we investigated the effect of Awa-tea on NFAT-mediated IL-9 gene expression in RBL-2H3 cells.…”
Section: Effect Of Wge and Awa -Tea On Ionomycin -Induced Il-9 Gene Ementioning
confidence: 84%
See 2 more Smart Citations
“…Antihistamines are widely used as allergy treatments because they inhibit histamine signalling by blocking H1R or suppressing H1R signalling as inverse agonists [12]. Long-term treatment with antihistamines can decrease H1R gene expression to the basal level [13]. It is hypothesised that after stopping long-term treatment, H1R blockade disappears relatively fast (the half-life of (levo)cetirizine is 6–10 h).…”
Section: Discussionmentioning
confidence: 99%